2017
DOI: 10.1080/17429145.2017.1373871
|View full text |Cite
|
Sign up to set email alerts
|

Plant defense approach ofBacillus subtilis(BERA 71) againstMacrophomina phaseolina(Tassi) Goid in mung bean

Abstract: This study was aimed to elucidate the mitigation mechanism of an endophytic bacterium, Bacillus subtilis (BERA 71) against Macrophomina phaseolina (Tassi) Goid disease in mung bean. M. phaseolina reduced the plant growth by inducing disease, hydrogen peroxide (H 2 O 2 ) and lipid peroxidation. The inoculation of B. subtilis to diseased plants increased chlorophyll, ascorbic acids, and superoxide dismutase, catalase, peroxidase, ascorbate peroxidase and glutathione reductase activities, and while inhibited H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 67 publications
(63 reference statements)
3
31
0
Order By: Relevance
“…PGPM influence plant growth and fitness by both direct and indirect mechanisms. Direct mechanisms include N 2 fixation, Fe sequestration, phytohormone production, and phosphate solubilisation, while major indirect mechanisms are antibiosis and production of lytic enzymes [3]. The beneficial effects on plant growth mediated by rhizospheric bacteria and fungi have been well documented [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGPM influence plant growth and fitness by both direct and indirect mechanisms. Direct mechanisms include N 2 fixation, Fe sequestration, phytohormone production, and phosphate solubilisation, while major indirect mechanisms are antibiosis and production of lytic enzymes [3]. The beneficial effects on plant growth mediated by rhizospheric bacteria and fungi have been well documented [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Several questions regarding the association of endophytic microorganisms with host plants, however, are still unanswered; including how long do they reside in the host and do they have any impact on photosynthesis. Abd_Allah et al [9] and Hashem et al [3] reported that the endophytic bacterium, Bacillus subtilis (BERA 71), enhances the photosynthesis and growth of chickpea ( Beta vulgaris L.) and mung bean via the production of phytohormones. Zhang et al [10] suggested that plant growth promoting rhizobacteria may function as a plant growth stimulator through an auxin-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination is regulated by sugars, nitrate, and phytohormones, such as auxin, cytokinins, ethylene, abscisic acid (ABA), GAs, brassinosteroid (BR) and light [12,13]. Salt deposition in soil decreases the osmotic potential of the growth medium for plants and reduces the water availability [14]. Plants respond to saltinduced osmotic stress by closing their stomata, thus limiting the loss of cellular water content and gas exchange, which reduces the photosynthetic rate.…”
Section: Phosphorus Mobilising Bacteriamentioning
confidence: 99%
“…This biotic stress leads towards the over accumulation of toxic reactive oxygen species (ROS) thus inducing oxidative stress in plant ( Vellosillo et al, 2010 ). Excess accumulated ROS interacts with the cellular constituents including lipids, proteins and nucleic acids, thus hinders the normal working of the cell ( El-Rahman et al, 2012 , Egamberdieva et al, 2017 , Hashem et al, 2017 ). One of the biotic stress induced by Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%